2019
DOI: 10.1177/0192623318822301
|View full text |Cite
|
Sign up to set email alerts
|

Thymomas and Associated Hyperplastic Lesions in Wistar Hannover Rats

Abstract: Thymomas occur prevalently in aged Wistar Hannover (WH) rats, along with hyperplastic lesions that cannot be categorized as thymomas. We compared the histological features of hyperplastic lesions and thymomas in WH rats, the incidences of these lesions, and the relationship of these lesions to the degree of thymic involution and also compared these lesions with those of Sprague Dawley (SD) rats in 4-, 13-, 26-, and 104-week studies. There were no morphological differences between hyperplastic cells and benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…One tumor showed a marked expansion with compression of unaffected tissue, and its histological structure resembled normal thymic architecture consisting of cortex-like (lymphocyte-rich) and medulla-like (epithelial cell-rich) areas ( Fig. 1E and F) as previously reported 10 . Neoplastic cells were immunohistochemically positive for cytokeratin 18 (Fig.…”
supporting
confidence: 77%
“…One tumor showed a marked expansion with compression of unaffected tissue, and its histological structure resembled normal thymic architecture consisting of cortex-like (lymphocyte-rich) and medulla-like (epithelial cell-rich) areas ( Fig. 1E and F) as previously reported 10 . Neoplastic cells were immunohistochemically positive for cytokeratin 18 (Fig.…”
supporting
confidence: 77%
“…Thymomas appear grossly as a firm, smooth mass in the anterior mediastinum, and compression of the surrounding tissues may or may not be present, depending on the size of the tumor. These tumors are rare in humans and most lab animals, with the exception of the Praomys ( Mastomys ) natalensis , 14 also known as the multimammate rat or common African rat; WH rats 10 ; several inbred strains of rats (BUF/Mna, 15 WAB, 16 and W/Nhg 17 ); European hamsters 18 ; and transgenic mice (SV40T 19 and E2F2 20 ). In the Fischer 344/N rat, thymomas are rare and are said to occur with no apparent sex difference, 8 and in this review, there were slightly more thymomas observed in male F344/N rats than in females.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A recent large study examined the incidences and histological features of thymomas and hyperplastic lesions in Wistar Hannover (WH) rats and found a high incidence of both lesions in this strain, with higher incidences observed in females than males. 10 Additionally, the authors found a higher incidence of these proliferative lesions in WH rats than in SD rats. The literature contains no reports of large studies of thymoma in Fischer 344 rats.…”
Section: Introductionmentioning
confidence: 93%
“…Thymoma, a prevalent tumor in Wistar Hannover (WH) rats, has an incidence of 5% in males and 15% in females as shown in our previous report. 1 In that study, we reported a higher incidence of thymic hyperplasia and thymomas in WH rats compared to Sprague Dawley rats and presented the histopathological features of hyperplasia and thymomas. Moreover, we found that the structure of the thymomas in WH rats consisting of the cortex and medullary differentiation (MD) areas resembled the normal thymic architecture.…”
Section: Introductionmentioning
confidence: 87%
“…The histological differences between hyperplastic lesions and thymomas were based on the size of the proliferative areas and the number of LyR and MD areas and pale-staining cell foci. 1 In the thymic proliferative lesions, the proliferative cells originated from the thymic epithelial cells in both cortex-like LyR and MD areas; however, it was difficult to recognize the proliferative thymic epithelial cells in the cortex-like LyR area due to the prominently increased number of lymphocytes observed in hematoxylin and eosin–stained specimens. 2 There are various types of thymic epithelia in the normal thymus, such as cortical, medullary, and subcapsular types.…”
Section: Introductionmentioning
confidence: 99%